Bahasa Inggris - Rahman, Rafika Rizky Aulia; Iswara, Rizka (Indonesian Law Journal, 2024)
The migration of a group of people to another country's territory has become a multidimensional phenomenon, as has the development of world politics. The arrival of the Rohingya community represents a conflict that the international community, including Indonesia, is currently grappling with. The influx of Rohingya refugees and asylum seekers, a result of the conflict in Myanmar, presents a new challenge for Indonesia. Although Indonesia did not ratify the 1951 Refugee Convention, it accepted their arrival as a form of concern for the humanitarian problems that occurred. However, this has led to tensions between Indonesian citizens and Rohingya, necessitating the state's intervention to resolve them. This article adopts a normative approach by synchronizing applicable legal provisions with field practices. Legal sources, books, and credible research results provide the data for this article. This research seeks to understand Indonesia's role and responsibility in managing Rohingya, who are foreign refugees on its territory, and offers practical suggestions and solutions to address existing issues. Keywords: Humanity, Refugees, Rohingya, Sovereignty